2014
DOI: 10.5194/isprsarchives-xl-5-573-2014
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of multi-view 3D reconstruction of a rock wall using several cameras and a laser scanner

Abstract: ABSTRACT:This work presents a comparative study between multi-view 3D reconstruction using various digital cameras and a terrestrial laser scanner (TLS). Five different digital cameras were used in order to estimate the limits related to the camera type and to establish the minimum camera requirements to obtain comparable results to the ones of the TLS. The cameras used for this study range from commercial grade to professional grade and included a GoPro Hero 1080 (5 Mp), iPhone 4S (8 Mp), Panasonic Lumix LX5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
1
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 8 publications
1
56
1
3
Order By: Relevance
“…Several studies have shown that SfM can generate highly‐accurate and high‐resolution DTMs more efficiently and cost‐effective than laser‐based alternatives in suitable environments (Niethammer et al , ; James and Robson, ; Nouwakpo et al , ). Accuracy of SfM‐derived data has been evaluated previously by comparing results to data derived from traditional photogrammetry (James and Robson, ; Rosnell and Honkavaara, ; Welty et al , ), ALS (Fonstad et al , ; Dietrich, ), TLS (Castillo et al , ; James and Robson, ; Westoby et al , ; James and Quinton, ; Gómez‐Gutiérrez et al , ; Thoeni et al , ; Micheletti et al , ; Nouwakpo et al , ; Smith and Vericat, ), and terrestrial topographic surveys (Fonstad et al , ; Javernick et al , ; Woodget et al , ; Smith and Vericat, ). These comparisons promote the utility of SfM, which is rapidly becoming part of the geomorphologist's toolbox (Gomez, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that SfM can generate highly‐accurate and high‐resolution DTMs more efficiently and cost‐effective than laser‐based alternatives in suitable environments (Niethammer et al , ; James and Robson, ; Nouwakpo et al , ). Accuracy of SfM‐derived data has been evaluated previously by comparing results to data derived from traditional photogrammetry (James and Robson, ; Rosnell and Honkavaara, ; Welty et al , ), ALS (Fonstad et al , ; Dietrich, ), TLS (Castillo et al , ; James and Robson, ; Westoby et al , ; James and Quinton, ; Gómez‐Gutiérrez et al , ; Thoeni et al , ; Micheletti et al , ; Nouwakpo et al , ; Smith and Vericat, ), and terrestrial topographic surveys (Fonstad et al , ; Javernick et al , ; Woodget et al , ; Smith and Vericat, ). These comparisons promote the utility of SfM, which is rapidly becoming part of the geomorphologist's toolbox (Gomez, ).…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of the high-resolution 3D model produced by such solutions is comparable to more expensive photogrammetric and Lidar techniques (Thoeni et al, 2014;Javernick et al, 2014;Remondino et al, 2012). Therefore it is very straightforward to adapt such techniques to underwater 3D modelling.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is lower in instrument costs compared to light detection and ranging technology (LiDAR), and has lower requirements on user expertise to create a geometrical 3D model thanks to the high level of automation in image processing. Additionally, in different fields of the geosciences (James and Robson, 2014;Thoeni et al, 2014;Piermattei et al, 2015;Smith and Vericat, 2015;Stumpf et al, 2015) it was shown that accuracy and resolution obtained are comparable to those obtained by LiDAR. However, as reported in the investigations on error sources and obtained precision by (Wackrow and Chandler, 2011;James and Robson, 2012;Micheletti et al, 2014;Nocerino et al, 2014;Bemis et al, 2014) the quality of the photogrammetric results depends principally upon (i) the camera network geometry and (ii) control data.…”
Section: Introductionmentioning
confidence: 62%